1999
DOI: 10.1038/sj.onc.1202695
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 MAP kinase increases okadaic acid mediated AP-1 expression and DNA binding but has no effect on TRE dependent transcription

Abstract: By performing in vitro kinase assays we found in papilloma producing 308 mouse keratinocytes that okadaic acid elevated activities of extracellular signalregulated kinase (ERK) 1/2, c-Jun N-terminal kinases (JNKs) and p38 mitogen-activated protein kinases (MAPKs). This okadaic acid mediated activation of MAP kinases correlated with increased AP-1 binding to a consensus TPA responsive element (TRE) and elevated TRE dependent transcription. To determine the role of p38 MAP kinases in these processes we employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
4
7
0
1
Order By: Relevance
“…The latter finding concurs with earlier observations made in other cell systems wherein inhibition of p38 MAPK was also found to enhance ERK1/2 phosphorylation and thereby augment ERK1/2-mediated cellular responses. [23][24][25][26] These previous findings, together with our current observations, are consistent with the concept that p38 MAPK negatively regulates the ERK1/2 signaling pathway. Supporting this concept, a direct 1-way cross-talk between p38 MAPK and ERK1/2 was recently demonstrated, wherein phosphorylated p38a was found to couple with ERK1/2 and thereby sterically block ERK1/2 phosphorylation by MEK1/2, 22 and possibly also act via a protein kinase that lies upstream of MEK1/2.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The latter finding concurs with earlier observations made in other cell systems wherein inhibition of p38 MAPK was also found to enhance ERK1/2 phosphorylation and thereby augment ERK1/2-mediated cellular responses. [23][24][25][26] These previous findings, together with our current observations, are consistent with the concept that p38 MAPK negatively regulates the ERK1/2 signaling pathway. Supporting this concept, a direct 1-way cross-talk between p38 MAPK and ERK1/2 was recently demonstrated, wherein phosphorylated p38a was found to couple with ERK1/2 and thereby sterically block ERK1/2 phosphorylation by MEK1/2, 22 and possibly also act via a protein kinase that lies upstream of MEK1/2.…”
Section: Discussionsupporting
confidence: 95%
“…This consideration appeared consistent with the findings in recent reports that demonstrated a negative regulatory interaction between the ERK1/2 and p38 MAPK signaling pathways, wherein p38 MAPK activation was found to inhibit ERK1/2 signaling 22 and, conversely, inhibition of p38 MAPK was shown to activate ERK1/2. [23][24][25][26] To address the latter mechanism herein, we examined the separate effects of inhibition and stimulation of p38 MAPK on Der p 1-induced activation of ERK1/2. As exemplified by the Western blots depicted in Fig 6 (top panel), relative to tissues that were not pretreated with the p38 MAPK inhibitor, Der p 1-exposed ASM tissues pretreated with SB202190 displayed distinctly enhanced time-related expression of phosphorylated ERK1/2.…”
Section: Role Of Mapks In Regulating Der P 1-induced Changes In Asm Rmentioning
confidence: 99%
“…6B). As reported by previous studies (27), blocking of p38 activity by the p38 inhibitor SB 202190 stimulated DCA-induced ERK activation and p38 phosphorylation (Fig. 6, A and B).…”
Section: Analyses Of Bile Acid Response Elements In the Humansupporting
confidence: 56%
“…We have found that this GST-Elk-1 fusion protein binds only activated (dual phosphorylated) ERK, and does not bind either resting or activated JNK (data not shown). Incorporation of 32 P into all substrates was found to be linear with time over the course of the in vitro kinase reactions and sensitive to differences in enzyme activity, as established by SDS-PAGE and autoradiography. Dualspecific phosphorylation of p38 indicative of its activation was detected using phospho-p38 MAPK (Thr 180 /Tyr 182 ) Ab obtained from New England Biolabs (Beverly, MA) to probe a Western blot.…”
Section: In Vitro Kinase Assays and Ex Vivo Detection Of Phosphoproteinsmentioning
confidence: 95%